Fatty acid metabolism shapes immune responses in chronic lymphocytic leukemia - Yang Zhang; Jun Ma; Peipei Li; Kang Lu; Yang Han; Xinting Hu; Xiaosheng Fang; Xin Wang; Ya Zhang (Biomarker Research)
Abstract Background Fatty acids serve as a crucial energy source for tumor cells during the progression of chronic lymphocytic leukemia (CLL). The present study aims to elucidate the characteristics of fatty acid metabolism (FAM) in CLL, construct a related prognostic score, and investigate the regulatory role and mechanisms of FAM in CLL development. Methods Bulk RNA sequencing data from CLL patients and healthy controls were analyzed to identify differentially expressed fatty acid metabolic genes. FAM-score was constructed using Cox-LASSO regression and validated. Single-cell RNA sequencing was used to analyze the expression of key FAM genes in CLL immune cell subsets and investigate cellular communication. Functional assays, including cell viability, drug sensitivity, and oxygen consumption assays, were performed to assess the impact of fatty acid oxidation (FAO) inhibition on CLL cells. Results Three FAM-related genes (LPL, SOCS3, CNR1) were identified with independent prognostic significance to construct the risk score. The FAM-score demonstrated superior prognostic performance compared to the Binet stage and was associated with established clinical prognostic markers. Single-cell analysis revealed distinct expression patterns of LPL, SOCS3, and CNR1 across CLL immune cell subsets. Cellular communication analysis highlighted the regulatory role of distinct B cell and Treg subsets in the CLL microenvironment. CLL patients with high FAM-score displayed distinct immune infiltration patterns, with increased FAO pathway activity. Inhibition of FAO reduced CLL cell viability, synergistically enhanced the efficacy of the PI3K inhibitor idelalisib. Conclusion The present study constructed a prognostic risk score based on FAM gene expression, revealing related immune phenotypic differences and exploring the regulatory role of FAO in CLL development. Targeting fatty acid metabolism potentially modulates the CLL immune microenvironment and synergistically enhances the efficacy of PI3K inhibitors.